Acute stress disrupts intestinal homeostasis via GDNF‐RET. (17th August 2020) - Lin, Lin; Feng, Bingcheng; Zhou, Ruchen; Liu, Yi; Li, Lixiang; Wang, Kairuo; Yu, Yanbo; Liu, Chao; Long, Xin; Gu, Xiang; Li, Bing; Wang, Xiaojie; et al.
Abstract: Objectives: Enterochromaffin (EC) cells have been associated with functional gastrointestinal disorders such as IBS. Recently, we found that glial cell‐derived neurotrophic factor (GDNF)‐rearranged during transfection (RET) localized in EC cells in human colonic epithelia. Here, we examine the role of GDNF‐RET in the pathophysiology of diarrhoea‐predominant irritable bowel syndrome (IBS‐D). Materials and Methods: GDNF was assessed by ELISA and immunohistochemistry in biopsies from IBS‐D patients and healthy controls. Stress was induced by using a wrap‐restraint stress (WRS) procedure to serve as an acute stress‐induced IBS model. The function of GDNF‐RET axis to intestinal stem cell (ISC) homeostasis, and EC cell numbers were assessed in vivo and in vitro. Results: GDNF‐RET was expressed in EC cells in human colon. GDNF was significantly increased in IBS‐D patients. WRS mice showed increased GDNF‐RET levels in colon. WRS induced visceral hypersensitivity by expanding of ISC and differentiation of EC cell via GDNF‐RET. Furthermore, GDNF‐treated mice recapitulated the phenotype of WRS mice. In vitro, GDNF treatment amplified Wnt signal and increased serotonin levels in colonic organoids in a dose‐dependent manner. Conclusions: We identified GDNF‐RET was presented in colonic epithelium of patients with IBS‐D. GDNF‐RET played important roles in regulating ISC and EC cell differentiation. Our findings, thus, provide RET inhibitor as new therapeutic targets for treatment of patients with IBS‐D. Abstract : GDNF‐RET was expressed in enterochromaffin (EC) cells in human colon. GDNF protein levels were increased in IBS‐D patients. GDNF‐RET indirectly promotes intestinal stem cell (ISC) proliferation through Wnt signal. GDNF‐RET promotes differentiation of ISC, leading to increased density of EC cells in acute stress model.